Frequency of Thrombocytopenia in Newborn with Birth Asphyxia - Asad ur Rehman; Khan, Erum Saleem; Naseem, Shabnam; Ahmed, Zubair (Indus Journal of Bioscience Research, 2025)
Background: Thrombocytopenia is a frequent hematologic perturbation in term neonates with birth asphyxia that may cause life-threatening hemorrhagic complications. Establishing risk factors among the mother and the neonate facilitates early diagnosis and treatment, particularly in settings that are short of resources where early intervention may be life-saving. Objective: To determine the frequency of thrombocytopenia in newborn with birth asphyxia. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from August 2024 to January 2025 at the Department of Pediatric Medicine, Combined Military Hospital, Rawalakot. Methodology: A total of 93 neonates with birth asphyxia, aged 1–25 days and with gestational age between 37 and 41 weeks, were included using non-probability consecutive sampling. Thrombocytopenia was defined as a platelet count below 150 × 10⁹/L. Clinical and demographic data were collected, including maternal conditions such as hypertension, diabetes, thrombocytopenia, mode of delivery, and antenatal care adequacy. Neonatal factors included gender, gestational age, birth weight, Apgar score, and clinical features of hypoxic-ischemic encephalopathy. Results: The mean age of neonates was 14.27 ± 7.47 days, with a mean gestational age of 39.01 ± 0.91 weeks and platelet count of 201.55 ± 107.77 ×10⁹/L. Thrombocytopenia was observed in 45.2% of cases. Significant associations were found with maternal hypertension (p<0.001), maternal thrombocytopenia (p=0.021), prolonged labor (p=0.014), and adequacy of antenatal care (p=0.001). Conclusion: Thrombocytopenia has a common association with birth asphyxia. Maternal hypertension, thrombocytopenia, and prolonged labor are strong risk factors.